Observations about the seismic response of RC buildings in Mexico City. Issue 2 (December 2020) - Alcocer, Sergio; Behrouzi, Anahid; Brena, Sergio; J Elwood, Kenneth; Irfanoglu, Ayhan; Kreger, Michael; Lequesne, Rémy; Mosqueda, Gilberto; Pujol, Santiago; Puranam, Aishwarya; Rodriguez, Mario; Shah, Prateek; et al.
Over 2000 buildings were surveyed by members of the Colegio de Ingenieros (CICM) and Sociedad Mexicana de Ingenieria Estructural (SMIE) in Mexico City following the Puebla-Morelos Earthquake of 2017. This inventory of surveyed buildings included nearly 40 collapses and over 600 buildings deemed to have structural damage. Correlation of damage with peak ground acceleration (PGA), peak ground velocity (PGV), predominant spectral period, building location, and building properties including height, estimated stiffness, and presence of walls or retrofits was investigated for the surveyed buildings. The evidence available suggests that (1) ground motion intensity (PGV) drove the occurrence of damage and (2) buildings with more infill and stiff retrofit systems did better than other buildings.